ALIENATION IN HARUKI MURAKAMI'S BLIND WILLOW, SLEEPING WOMAN - Imam, - (2016)
This study explores alienation in Haruki Murakami's Blind Willow, Sleeping Woman. It studies the aspects of alienation in three selected short stories from Blind Willow, Sleeping Woman: "A Folklore for My Generation: A Pre-History of Late-Stage Capitalism," "Tony Takitani," and "Firefly," and how these aspects manifest in the lives of the people in the selected stories. To achieve the objectives, the study was conducted under postmodernist approach and employs Seeman's theory on alienation known as Seeman's Aspects of Alienation (1959) as the theoretical framework of the study. The findings divulge that there are four alienation aspects palpable in the selected short stories: powerlessness, meaninglessness, normlessness, and social isolation. They also disclose that the alienation aspects found manifest through four key points i.e. the unknown origins of alienation, the problem of choices overload, the fragmentation of life aspects, and disconnected relational self. Viewed from postmodern perspective, Murakami's Blind Willow, Sleeping Woman can be interpreted as a representation of contemporary Japan as it portrays contemporary alienation issues, which are the effects of the breaking down of the Japanese traditional norms establishment, the grand narrative, in at least two occasions in Japanese history, Japan's involvement and defeat in World War II and the student movement in the sixties.;--- Penelitian ini menelaah alienasi dalam kumpulan cerpen Blind Willow, Sleeping Woman karya Haruki Murakami. Persisnya, penelitian ini mengkaji aspek-aspek alienasi dalam tiga cerpen terpilih di dalamnya yakni "A Folklore for My Generation: A Pre-History of Late-Stage Capitalism," "Tony Takitani," dan "Firefly," dan bagaimana aspek-aspek ini terbentuk dalam kehidupan orang-orang dalam ketiga cerita yang dipilih. Demi mencapai tujuan tersebut, penelitian ini menggunakan pendekatan posmodern dan teori Seeman yang dikenal dengan Aspek Alienasi Seeman (1959) sebagai kerangka teoretis. Hasil temuan menunjukkan bahwa ada empat aspek alienasi yang nampak dalam cerita yang dipilih yakni ketidakberdayaan, ketiadaan makna, pengingkaran norma, dan isolasi sosial. Juga didapati bahwa aspek alienasi yang ditemukan terbentuk melalui empat faktor utama yakni sumber alienasi yang tidak diketahui, problematika membludaknya pilihan, fragmentasi aspek kehidupan, dan diri relasional yang terputus dari substansi sosial. Ditinjau melalui perspektif posmodern, Blind Willow, Sleeping Woman karya Murakami dapat diartikan sebagai sebuah representasi atas Jepang kontemporer karena ia membingkai isu-isu alienasi kontemporer, yang merupakan produk dari pemecahan norma tradisional Jepang, dengan kata lain pemecahan narasi besar, setidaknya pada dua peristiwa sejarah Jepang: keterlibatan dan kekalahannya dalam Perang Dunia Kedua dan gerakan pemuda pada tahun enampuluhan.